Effect of Salt Reduction on Dough Handling and the Breadmaking Quality of Canadian Western Red Spring Wheat Varieties. Issue 4 (3rd May 2017) - Yovchev, Aleksandar G.; Briggs, Connie; Stone, Andrea K.; Hucl, Pierre; Nickerson, Michael T.; Scanlon, Martin G.
Abstract : The effect of salt (NaCl) on the breadmaking quality of 37 varieties of Canadian Western Red Spring wheat ( Triticum aestivum L.) was investigated along with dough stickiness for a 20 variety subset. A principal components analysis indicated that dough development time (DDT), mixing tolerance index (MTI), and stability (STA) were highly correlated. DDT showed an inverse relationship with MTI ( r = –0.73) and a positive relationship with STA ( r = 0.89). STA was also negatively related to MTI ( r = –0.76). A reduction of salt from 2.0 to 1.1% (based on flour weight) was considered from a practical perspective. Each variety responded differently to salt reduction. Obtaining an optimal dough consistency with less salt required less work input and shorter mixing time. Overall, decreasing loaf volume with reducing salt content was observed, although certain varieties produced the opposite effect. This suggests that for a particular flour, depending on the inherent flour strength, there is a level of NaCl that produces an optimum between gluten strength and gas‐holding capacity of the dough, resulting in a loaf with good crumb texture and an even distribution of bubble sizes. A stickiness test was performed on selected varieties to evaluate the dough handling properties at 1.1 and 2.0% salt levels. The overall trend showed an increase in stickiness with a decrease in the salt content; however, certain varieties showed no change.